تأثير مسؤوليات مجلس الإدارة على جودة المعلومات المحاسبية: (The Effect of the Responsibilities of the Board of Directors, on the Quality of Accounting Information) - Hamd, Nagi; Lubis, Asmuliadi; Mohd Balwi, Mohd Abd Wahab Fatoni (Online Journal of Research in Islamic Studies, 2023)
Based on the world’s crises over the last two decades, international bodies have sought to establish rules that govern commercial banks’ standards of control and supervision. Although the banking sector is the backbone of economic life, governance has evolved over the last decade to include more transparency in management and regulate the relationship between the company’s parties. Furthermore, to achieve a high level of quality in these reports, more trust should be placed in the information in these companies’ financial reports. The problem statement addresses the effect of applying corporate governance standards of the responsibilities of the board of directors on the performance of Libyan commercial banks. The study aims to determine the effect of this standard’s implementation on the quality of accounting information in Libyan commercial banks. In order to achieve the study’s objectives, the questionnaire was used to collect data and assess the impact of applying standards of the responsibilities of the board of directors of corporate governance on the quality of accounting information. The Organization for Economic Cooperation and Development criterion was used as an independent variable, standards of the responsibilities of the board of directors, to measure it on the dependent variable (the quality of accounting information in banks). The study sample included several members of the board of directors, non-auditors, internal auditors, accountants and heads of departments in some branches of Libyan commercial banks. The descriptive approach was used in the analysis using the SPSS program. The study concluded that this governance standard positively impacts Libyan commercial banks’ accounting information quality. However, this result was strong in the responsibilities of the board of directors on the quality of accounting information, in contrast to this study’s standards and to previous studies. Comparing earlier research, it was found that the environment in which Libyan banks operate is different from that of these studies because Libyan banks confront a variety of hazards, including those related to the environment, the economy, politics, and security. The study also recommended that: the Central Bank should verify the banks’ implementation of the Governance Guide issued by the Central Bank of Libya. Banks must have a guide to corporate governance principles and a committee responsible for ensuring compliance with the practice of these principles.